ANALISIS KINERJA KEUANGAN PT. BANK MUAMALAT INDONESIA, Tbk. PERIODE 2009-2011 (PERBANDINGAN RASIO-RASIO KEUANGAN DAN ECONOMIC VALUE ADDED) - Nalim (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2014)
The performance of Bank Muamalat Indonesia (BMI) in 2011 increases its value continually for the stakeholders and contributes in national syariah banking development. Therefore, it is very important to analyze the financial performance in order to get the real description of the company. General financial analysis can be conducted by analyzing the financial ratio and Economic Value Added (EVA) approach. The result of the research shows that the best performance of BMI was in 2010 based on CAR and NPM values. According to ROA, ROE, and BOPO indicators, the best performance was in 2011. The EVA analysis shows that EVA value in the period of 2009-2011 was less than zero, which means that the best performance was not in the year. After getting the result of the financial ratio and EVA analysis, there is comparison between the interpretations of those financial performance results. The result of the comparison is significant. By using financial ratio approach, it shows that the bank has good remunerativeness. However, based on EVA analysis, the EVA value is less than zero, which means that BMI performance is not good. It can be concluded that the good performance based on financial ratio may become not good performance if we analyze it using EVA analysis.